Retention of an Irregular Feature Specification as a Source of Functional Misarticulation (Philologia, 2021)
The present study attempts to analyze the phonological system of a japanese- speaking child with a very idiosyncratic functional (non-organic) speech disorder, wherein a target back rounded vowel is always replaced by a bilabial nasal. First, I examine the feature specifications of the two segments and argue that they share a phonological feature [Labial] in the hierarchical organization of distinctive features. Focusing on the substitution pattern and its theoretical consequence under Optimality Theory, I then discuss that in the child’s system a markedness constraint which prohibits a labial vowel outranks opposing faithfulness constraints, resulting in the appearance of the target vowel being replaced by the labial nasal; the substitution is triggered by wrong specifications of the related features. I further argue that the constraint ranking results in creating illegitimate prosodic structures, as well as misproduction of the target segment per se. Finally, it is suggested that the retention of such irregular feature specifications in phonological development is common across languages and that it can be a source of functional misarticulation.
Keywords: honological development; speech disorder; functional misarticulation; feature geometry; Optimality Theory